2022
DOI: 10.3390/md20070445
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed Phenolics as Natural Antioxidants, Aquafeed Additives, Veterinary Treatments and Cross-Linkers for Microencapsulation

Abstract: Driven by consumer demand and government policies, synthetic additives in aquafeed require substitution with sustainable and natural alternatives. Seaweeds have been shown to be a sustainable marine source of novel bioactive phenolic compounds that can be used in food, animal and aqua feeds, or microencapsulation applications. For example, phlorotannins are a structurally unique polymeric phenolic group exclusively found in brown seaweed that act through multiple antioxidant mechanisms. Seaweed phenolics show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 212 publications
(361 reference statements)
1
20
0
1
Order By: Relevance
“…pavonica has demonstrated higher antioxidant activity despite its low total phenolic content compared to the other samples. These findings suggest that coextracted bioactive compounds with antioxidant potencies, such as sulfated polysaccharides, tocopherols, proteins or peptides, and carotenoid pigments, may possess inherent antioxidant properties . Wang et al investigated the AOA of Palmaria palmata extract obtained by using carbohydrase and protease enzymes and reported that enzyme-assisted extract indicated higher AOA than conventional extract.…”
Section: Resultsmentioning
confidence: 99%
“…pavonica has demonstrated higher antioxidant activity despite its low total phenolic content compared to the other samples. These findings suggest that coextracted bioactive compounds with antioxidant potencies, such as sulfated polysaccharides, tocopherols, proteins or peptides, and carotenoid pigments, may possess inherent antioxidant properties . Wang et al investigated the AOA of Palmaria palmata extract obtained by using carbohydrase and protease enzymes and reported that enzyme-assisted extract indicated higher AOA than conventional extract.…”
Section: Resultsmentioning
confidence: 99%
“…as reported previously [ 65 ]. Some commercial seaweed fertilizer contains phenolic compounds, which have anti-microbial activity and may act as a barrier against plant diseases [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several different classes of natural products or secondary metabolites derived particularly from plants or microbes have been associated with varying phytotoxic activities (Table 2). Seaweeds have been shown to be a rich source of these bioactive compounds, as well as being prolific producers of more diverse and complex biomolecules (Gómez-Guzmán et al 2018; Gunathilake et al 2022; Salehi et al 2019; Santos et al 2019). This indicates that further exploration into establishing seaweed phytotoxic potential and an increased effort in the development or formulation of seaweed-derived bioherbicides would likely yield desirable/positive outcomes.…”
Section: Bioherbicidesmentioning
confidence: 99%
“…Interestingly, several studies have reported terpenoids/terpenes, phenolics, fatty acids and steroids as groups of bioactive compounds associated with phytotoxic activities (Araniti et al 2017; Espinosa-Colín et al 2023; Feitoza et al 2018; Pardo-Muras et al 2020, 2022). Seaweeds are known to produce these bioactive compounds (Gómez-Guzmán et al 2018; Gunathilake et al 2022; Salehi et al 2019; Santos et al 2019), which points to their capacity to serve as rich natural sources for novel bioherbicide formulation/development. This is also supported by several reports that have uncovered the allelopathic inhibitory effects of seaweeds on the same or other seaweed species, as well as other varying organisms occurring within the natural environment (Andras et al 2012; Rasher and Hay 2010; Rasher et al 2011; Sudatti et al 2020; Vieira et al 2016; Ye and Zhang 2013).…”
Section: Introductionmentioning
confidence: 99%